Modulation of Macrophage Function by Lactobacillus-Conditioned Medium - Nanjundaiah, Yashaswini Seenappanahalli; Wright, David A.; Baydoun, Anwar R.; Khaled, Zahangir; Ali, Zulfiqur; Dean, Paul; Sarker, Mosharraf H. (Frontiers in Cell and Developmental Biology, 2020)
Probiotics are used as microbial food supplements for health and well-being. They are thought to have immunomodulatory effects although their exact physiological mechanism of action is not clear. This study investigated the influence of probiotic Lactobacillus rhamnosus GG conditioned media (LGG-CM) on macrophage phagocytosis of non-pathogenic E. coli HfrC. The gentamicin protection assay was used to study the bacterial killing phases of phagocytosis. Macrophages co-incubated with E. coli for an hour allowed them to ingest bacteria and then the rate of E.coli killing was monitored for up to 300 minutes to determine the killing or digestion of the bacteria by recovering them from the macrophage lysate. We found that the LGG-CM significantly increased the bacterial killing by approximately 6-fold when compared with that of controls. By contrast, this killing process was found to be due the enhanced free radical production via the activation of NADPH oxidase, stimulated by the LGG conditioned medium. We also found that the conditioned medium had small effect on nitric oxide generation, albeit to a lesser extent. This work suggests that LGG-CM may play an important role in suppressing the total microbial load associated within the macrophages and hence, the extent to which pro-inflammatory molecules such as free radicals and nitric oxide (NO) are generated. This modulation of inflammation promoting signals by LGG-CM may be beneficial as it modulates bacterial uptake and digestion, and there by prevents any collateral damage to host.